2022
DOI: 10.1002/pen.25957
|View full text |Cite
|
Sign up to set email alerts
|

Development of PA6/GO microspheres with good processability for SLS 3D printing

Abstract: The particle size and processability of the powder are the keys for successful nylon in selective laser sintering (SLS) 3D printing, but the nylon powders on the market have disadvantages such as uncontrollable particle size and large distribution, poor sphericity, and poor processability. In this study, graphene oxidehybridized polyamide 6 (PA6/GO) microspheres perfectly suitable for SLS 3D printing have been fabricated via reaction-induced phase separation. The selective distribution of GO in PA6 microsphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Meanwhile, PNCs have been fabricated with enhanced thermal and electrical conductivity, improved mechanical and thermal expansion, and increased fire retardancy for automotive, oil and gas, and other versatile applications 137–207 . Finally, it is emphasized that 3‐DPT and 4‐DPT are innovative processing technologies, presenting the future route of the manufacturing sector 208–244 …”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, PNCs have been fabricated with enhanced thermal and electrical conductivity, improved mechanical and thermal expansion, and increased fire retardancy for automotive, oil and gas, and other versatile applications 137–207 . Finally, it is emphasized that 3‐DPT and 4‐DPT are innovative processing technologies, presenting the future route of the manufacturing sector 208–244 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a very small amount of GO can change the non-absorption characteristics of NC to infrared radiation due to the good dispersion and good photo-thermal conversion capacity of GO nanosheets. [22,36,45] By further increasing the GO content, it can be found that the delay time is only tens of milliseconds when doping 2 wt% of GO. In addition, the average flame intensity of the propellants during selfsustaining combustion was calculated by dividing the total flame intensity by the burning time, and a downward trend is shown in Figure 9A.…”
Section: Laser Ignited Combustion Performance In Airmentioning
confidence: 99%